Prevalence and significance of iron deficiency of anaemia among people of Mornag District of Nepal - Sinha, Amar Kumar; Majumdar, Biswajit; Yadav, Shrawan Kumar (Journal of Nobel Medical College, 2012)
Iron deficiency anaemia is one of the most dangerous and devastating causative form of malnutrition in developing countries, where special care should be taken from the health community to address the problem in South East Asian countries, 1.3-2.2 billion population is affected according to world health organization. Fifty percent of women and children and 60% of gross anemic women of developing nations have been adversely affected till date. The most common cause of iron deficiency anaemia is due to inadequate intake of iron in diet, physiologic demands of pregnancy and rapid growth and loss due to parasitic infections. Other prevalent causes of anaemia include malaria, chronic infections and nutritional deficiencies of vitamin A, folic acid and Vitamin b-12. The study reveals that 25.57 % of patients have been suffering from iron deficient anemia. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7286 Journal of Nobel Medical College Vol.1(1) 2011 40-44